Development of the test of skills in conflict negotiation management - Vicuña P., Luis (2008)
The present report reports to the scientific community the product of the elaboration of the test of abilities for the management in the negotiation of conflicts, whose objective is to determine the abilities to manage the management of conflicts successful; part that this is the result of the complex interaction of five abilities: communication, commitment, perspective, emotional control, and empathy; on the basis of these supposed factors the test was constructed, the one that was put to consideration of judges and statistic analyses of the behavior of its components within the whole, having found that the test measures what it sets out from the point of view of the judges and who the factors are parts that they significantly relate to the whole, his you see to know the error measurement was used the method of the test retest and the method of the internal consistency of Cronbach, by both methods the found coefficient surpasses to the 0,80. Of the found thing one concludes that the proposed factors proposed they underlie in the ability of management in the negotiation of the conflicts and the test measures within the allowed allowable error.